Study of the Immersion Freezing Theory Using the Classical Nucleation Framework - Mihalis Lazaridis (Atmosphere, 2022)
The classical nucleation theory for immersion freezing was used for the simulation of ice nuclei particle activation under atmospheric conditions. A modification of the surface diffusion energy was introduced that was based on the concept of a two-dimensional diffusion of the adsorbed molecules on the surface of the substrate. Comparison with available laboratory data for kaolinite dust and bacteria cells were performed and qualitative agreement of ice nucleation onset was found. Simulations were performed for specific airborne microorganisms including P. syringae. Additionally, model simulations were performed for a set of 140 different bacteria. Model simulations showed that bacteria activation occurs in the atmosphere, which may be enhanced at lower temperatures. Increasing pre-existing available surface for ice nucleation resulted in higher nucleation probability in agreement with experimental observations. The current study showed that a critical parameter for the determination of IN is the value of the contact angle between the substrate and the critical cluster. Comparison with available parameterizations for P. syringae and dust particles was also performed, and classical nucleation theory showed similar nucleation rates in the temperature range of laboratory experiments from which the parameterizations were derived. In addition, a correction factor to bulk surface tension was applied for small ice clusters. Higher nucleation rates were calculated from this correction by a few orders of magnitude but their effect on nucleation probability was not significant. The classical nucleation theory is based on physical principles and can be further incorporated in General Circulation Models to determine the IN activation in the atmosphere for a mixture of different pre-existing particles including bacteria cells and dust.